Laparoscopic management of iatrogenic lesions - Dos Santos Abreu, Leonardo de Albuquerque [UNESP]; Tanaka, Milton; de Abreu, Sidney Castro; Kawano, Paulo Roberto [UNESP]; Yamamoto, Hamilto Akihissa [UNESP]; Pereira Otsuka, Rodrigo Arthur [UNESP]; Travassos, Marcelo Rosa [UNESP]; Amaro, João Luiz [UNESP]; Fugita, Oscar Eduardo Hidetoshi [UNESP] (Mary Ann Liebert, Inc., 2008)
Purpose: To present our series of patients who underwent laparoscopic correction of iatrogenic lesions and a review of the literature.Patients and Methods: We evaluated 23 patients who underwent laparoscopic correction of iatrogenic lesions. Thirteen patients had open surgery, 6 had an endoscopic procedure, and 4 had a laparoscopic approach as the first surgical procedure. Vesicovaginal fistulas (VVF) developed in seven patients after open abdominal hysterectomies, and 1 patient presented with a VVF after ureterolithotripsy. A urethral cutaneous fistula developed in one patient after a laparoscopic resection of endometriosis nodules, and 1 patient presented with a ureterovaginal fistula after a perineoplasty. Three patients presented with encrusted ureteral stents after ureterolithotripsy. Ureteral stenosis developed in seven patients: three after open abdominal surgery, three after ureteroscopy, and one after pyeloplasty. One patient had a ureteral injury during laparoscopic partial nephrectomy, and two patients had bowel injuries after a tension-free vaginal tape procedure and a laparoscopic radical prostatectomy.Results: All patients underwent laparoscopic correction of the iatrogenic injuries. One patient had an early recurrence of a VVF, and one patient had a recurrence of a ureteral stenosis. There was one conversion to open surgery because of technical difficulties and one major bleeding event that necessitated blood transfusion. A lower limb compartmental syndrome developed in one patient.Conclusion: Despite the small number of patients and different types of surgeries performed, laparoscopic management of iatrogenic lesions seems to be feasible and safe in experienced hands. Its precise role in the management of this stressful condition still needs to be determined.